Development of ICT TPACK-oriented learning media for gymnastics material of Grade VIII Junior High School students - I Gusti Ngurah Bagus Rona Wisaka; Made Agus Wijaya; I Gede Suwiwa (Universitas Sriwijaya, 2023)
This study aims to develop an ICT-TPACK-oriented learning video for grade VIII students for forward and back-roll tasks. This research and development study uses the ADDIE model. The study population consisted of 2,582 students with 501 samples of grade VIII from 8 public junior high schools in the Buleleng District. Closed questionnaires in the form of google forms and motion task validation sheets were used as instruments with quantitative-qualitative descriptive analysis techniques. The results showed 1) 93% of students needed motion task videos, and 2) content expert scores on motion tasks reached 72 out of 75. In conclusion, 1) PE motion task videos on forward and back-roll material were needed by grade VIII students, and 2) the forward and back-roll tasks were valid. The motion tasks designed can be implemented by PE Junior High School teachers in Buleleng District.